1963
DOI: 10.1029/jz068i004p00997
|View full text |Cite
|
Sign up to set email alerts
|

Study of energetic electrons and their relationship to auroral absorption of radio waves

Abstract: The high-latitude boundary (LN) of energetic electrons (E • 40 key) quasi-trapped at an altitude of 1000 km was studied with the satellite Injun I over North America during periods of magnetic quiet and magnetic storms in 1961. The boundary was very sharp during disturbed periods, and it moved farther from the pole during larger disturbances. The electron intensity south of LN increased during magnetic disturbances, and the electron spectrum was much softer than normal just at the boundary. Throughout two magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1966
1966
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…-there has been interest in relating the absorption effects to the incoming energetic particles causing them: to identify the nature of the particles and their energy; to determine the height of the absorption which depends on the energy; to be able to predict one quantity from the other; and to learn the physics involved. Maehlum and O'Brien (1963) and McDiarmid et al (1963) raised statistical arguments based on the occurrence and location of auroral absorption and of energetic electron precipitation detected by the low-orbit satellites Injun I and Alouette I, to argue that the latter was likely to be the cause of the former. The first direct connection was demonstrated by Jelly et al (1964) using measurements of >40 keV electrons on the early Canadian satellite Alouette I when passing over, or close to, the field of view of wide-beam riometers operating at, or near to, 30 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…-there has been interest in relating the absorption effects to the incoming energetic particles causing them: to identify the nature of the particles and their energy; to determine the height of the absorption which depends on the energy; to be able to predict one quantity from the other; and to learn the physics involved. Maehlum and O'Brien (1963) and McDiarmid et al (1963) raised statistical arguments based on the occurrence and location of auroral absorption and of energetic electron precipitation detected by the low-orbit satellites Injun I and Alouette I, to argue that the latter was likely to be the cause of the former. The first direct connection was demonstrated by Jelly et al (1964) using measurements of >40 keV electrons on the early Canadian satellite Alouette I when passing over, or close to, the field of view of wide-beam riometers operating at, or near to, 30 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…The motion of low altitude trapping boundaries to lower latitudes during magnetic disturbances has been noted previously for 2 40 kev electrons (Maehlum and O'Brien, 1963) and for 2 280 kev electrons (Williams and Palmer, 1965). The fact that 2 40 kev and 2280 kev trapped electrons have the same nightside high latitude trapping boundary, (Williams and Mead, 1965) implies that the 140 kev electrons will also characteristically exhibit trapping boundary collapses during magnetic storms.…”
mentioning
confidence: 80%
“…So far, several authors have reported a good correlation between the CNA observed with broad-beam riometers and precipitating medium-energy electrons, by comparing with data from the low-altitude satellites (Maehlum and O'Brien, 1963;Hargreaves and Sharp, 1965;Parthasarathy et al, 1966;Jelly and Brice, 1967) and from a geostationary satellite (Collis et al, 1983(Collis et al, , 1984Collis and Korth, 1985). Some of them have also shown an empirical relationship between CNA and precipitating medium-energy electrons measured at low altitude (Hargreaves and Sharp, 1965;Parthasarathy et al, 1966) and at geosynchronous orbit (Collis et al, 1983).…”
Section: Introductionmentioning
confidence: 94%